The determinants of consumer acceptance on accessibility towards internet banking in Malaysia / Khairunnisa Hassan - Hassan, Khairunnisa (Faculty of Business and Management, 2011)
Internet banking is one of facilities served by banking institutions to their customers. Internet banking not only gave advantages to customers but also to banking institution. But, there are some individuals not really understand what type of service provides by internet banking. The past researcher shows that there are many factors that influence costumer’s using internet banking. Present research study revealed that there are three factors that influence consumer accessibility towards internet banking in Malaysia which are individual perception, technology system and also security. This study will be conducted at three different states which Selangor, Malacca and also Johor involved total of 50 respondents.